2021
DOI: 10.1002/ange.202104035
|View full text |Cite
|
Sign up to set email alerts
|

Ionische Flüssigkeiten und stark eutektische Lösungsmittel in der anorganischen Synthese

Abstract: Ionische Flüssigkeiten und stark eutektische Lösungsmittel sind für die ressourceneffiziente Synthese anorganischer Materialien von zunehmendem Interesse. Dieser Aufsatz thematisiert die chemischen Reaktionen vielfältiger stark eutektischer Lösungsmittel und verschiedener Typen von ionischen Flüssigkeiten, darunter metallhaltige, [BF4]−‐ oder [PF6]−‐basierte sowie chalkogenhaltige ionische Flüssigkeiten. Dies schließt Beispiele ein, in denen sowohl Kation als auch Anion im Endprodukt enthalten sind. Das Ziel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 207 publications
(474 reference statements)
0
4
0
Order By: Relevance
“…1,2 The IL may be a stable and inert solvent or it acts as a reactant that is altered by chemical reaction with the substances to be dissolved. 1–14 Sometimes ions or molecules of the IL are incorporated into the solid products. As a generally less expensive alternative to ILs, deep eutectic solvents (DES) have also been tested for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 The IL may be a stable and inert solvent or it acts as a reactant that is altered by chemical reaction with the substances to be dissolved. 1–14 Sometimes ions or molecules of the IL are incorporated into the solid products. As a generally less expensive alternative to ILs, deep eutectic solvents (DES) have also been tested for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…As a generally less expensive alternative to ILs, deep eutectic solvents (DES) have also been tested for this purpose. 1,4,13,15–19 Of course, large-scale use of ILs or DES only makes sense if they are affordable, are not altered during the reaction, and can be recycled efficiently. Regardless of commercial considerations, a broad knowledge base is required to optimize process parameters for a desired application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,10,13] Thus, contrary to most other solvents, ILs cannot always be regarded as inert reaction media. [19][20][21] Salts containing cations composed of pnicogen and chalcogen atoms are comparatively rare. In 1975, Gillespie et al reported the first cationic sulfidonitrogen rings.…”
Section: Introductionmentioning
confidence: 99%